Analisis Komponen Utama untuk Menilai Faktor Lingkungan Mikro dan Pertumbuhan Angsana pada Lahan Percobaan FABA di Banko Barat, Tanjung Enim - Maghzarini, Nessa Regitha; Setyawan, Dwi; Hanum, Herlina (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Maghzarini, N. S., Setyawan, D., & Hanum, H. (2024). Principal component analysis for micro environmental factor and angsana growth at FABA experimental plot in Banko Barat, Tanjung Enim. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 543–555). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Post-mining revegetation often uses highly adapted plant species to harsh conditions including those from legumes like Angsana (Pterocarpus indicus). Microenvironmental factors such as soil moisture, temperature, light, and soil pH affect plant growth. The research aimed to monitor the microenvironment and evaluate the response to plant growth on coal post-mine land. This research was conducted from October to November 2023 in the FABA (fly ash and bottom ash) IUP PIT 3 landfill in Banko Barat (Tanjung Enim). Field observation used a survey method. A random sampling of 39 plants was selected from 65 seedlings using the Slovin formula. Micro-environment measurement includes soil moisture, temperature, pH, and flux intensity. Plants were measured for stem diameter and plant height. Data obtained were analyzed using PCA (Principal Component Analysis). Soil moisture varied greatly from 25.3 to 90.7 %. Soil temperature ranged between 30.8 and 42.4°C. Light intensity differed widely between morning and afternoon measurements (35000 and 135000 lux respectively). In general plant height and stem diameter increased slowly. PCA indicates that 52.69% of data variance is related to soil temperature and stem diameter. There is a great variance between plant samples attributed to environmental factors and plant growth.